Convection of Agricultural Products Moisture Transfer During Drying - Abduganieva F.Z; Abduganiev J.Sh; Elmonov L.Kh (Peerian Journals Publishing, 2022)
In the article, the absorption of moisture on the surface of the product into the sorbent-hygroscopic material when the sorption-contact (due to mutual contact) method is used in the drying process of agricultural products, as a result of which the mass transfer process accelerates, depends on the moisture diffusion coefficient of the material, moisture retention and temperature gradients.
Keywords: Drying; convective; air temperature; humidity